2016
DOI: 10.1063/1.4944622
|View full text |Cite
|
Sign up to set email alerts
|

Giant Dirac point shift of graphene phototransistors by doped silicon substrate current

Abstract: Graphene is a promising new material for photodetectors due to its excellent optical properties and high-speed response. However, graphene-based phototransistors have low responsivity due to the weak light absorption of graphene. We have observed a giant Dirac point shift upon white light illumination in graphene-based phototransistors with n-doped Si substrates, but not those with p-doped substrates. The source-drain current and substrate current were investigated with and without illumination for both p-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 27 publications
0
33
1
Order By: Relevance
“…Most research has focused on enhancement of the responsivity using various methods, such as p-n junctions, 13,14 plasmonic resonance, 15,16 asymmetric electrodes, 17,18 optical cavities, 19 waveguides, 20,21 nanoribbons, 8,22 and optical gating. [23][24][25][26][27] However, although graphene is highly sensitive to the surrounding materials and its influence changes according to the wavelength, the photoresponse mechanism in the broadband wavelength region from visible to long-wavelength IR (LWIR) has been less studied. 28 In particular, the materials surrounding graphene have a strong effect on its optical properties.…”
Section: Broadband Photoresponse Of Graphene Photodetector From Visibmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research has focused on enhancement of the responsivity using various methods, such as p-n junctions, 13,14 plasmonic resonance, 15,16 asymmetric electrodes, 17,18 optical cavities, 19 waveguides, 20,21 nanoribbons, 8,22 and optical gating. [23][24][25][26][27] However, although graphene is highly sensitive to the surrounding materials and its influence changes according to the wavelength, the photoresponse mechanism in the broadband wavelength region from visible to long-wavelength IR (LWIR) has been less studied. 28 In particular, the materials surrounding graphene have a strong effect on its optical properties.…”
Section: Broadband Photoresponse Of Graphene Photodetector From Visibmentioning
confidence: 99%
“…28 In particular, the materials surrounding graphene have a strong effect on its optical properties. 24,25 It is thus important to investigate the effects of these materials experimentally to reveal the photoresponse mechanism of graphene photodetectors. We have previously investigated the influence of the surrounding materials for broadband photoresponse; 29 however, no direct evidence of the photogating induced by the substrate from the visible to LWIR wavelengths was demonstrated.…”
Section: Broadband Photoresponse Of Graphene Photodetector From Visibmentioning
confidence: 99%
“…24 We have previously investigated various techniques for this purpose, including the use of p-n junctions, 25 plasmonic metamaterial absorbers, [26][27][28] and the photogating effect. [29][30][31][32][33][34] Here, we report a detailed mechanism for the photogating effect that significantly improves the responsivity of graphene photodetectors operating in the MWIR spectral band.…”
Section: Introductionmentioning
confidence: 95%
“…These photoelectrons/holes are subsequently separated via the application of V bg . Second, the photoelectrons accumulate in the depletion layer at the TEOS/InSb boundary as a consequence of V bg , 29 and V bg is modulated by the internal electric field generated by the accumulated photoelectrons. Third, the field effect in the graphene is changed by the modulation of V bg .…”
Section: Photogating Modulation In Mwir Photoresponsementioning
confidence: 99%
“…17,18 Although various studies have revealed Schottky-barrier formation and carrier transport phenomenon in graphene and semiconductors including Si, [19][20][21][22][23][24][25][26][27] Ge, 28,29 GaAs, [30][31][32] CdSe, 33,34 SiC, 35,36 and GaN, 37,38 it is not clear how the extraordinary high responsivity is obtained in the heterojunction structure. We have proved the graphene/insulator layer region underwent photogating, 3,17,[39][40][41][42][43][44] which is one of the most effective responsivity enhancement candidates among possible techniques, such as pn junctions; 45 turbostacking of graphene; 40 plasmonic metamaterial absorbers; [46][47][48] the addition of photosensitizers including MoS 2 , 49,50 ZnO, 51,52 organic semiconductor, 53 and quantum dots; [54][55][56][57] and optical waveguides. 58 Photogating modulates the surface carrier density of graphene by locating a photosensitizer in the vicinity of the graphene.…”
Section: Introductionmentioning
confidence: 96%